REVIEW ON CHILD SAFETY WEARABLE DEVICE USING ARDUINO - Archana Kalyanrao Kale; Dr. A. M. Rawate; Dr.Syeda Sumera Ali (International Journal of Innovations in Engineering Research and Technology, 2021)
The main objective of this system is to provide the safety to child which is lost in major crowded area. Now a day, Childs are not secured they are facing many issues regarding their security. There are number of security systems for the child security purpose. In order to overcome such problems the child safety wearable system is implemented. This system is not required any expensive technology and it is user friendly for both educated and uneducated people. There are many wearable devices are available in the market to track the child using wi-fi and Bluetooth but the wi-fi and Bluetooth are the unreliable medium for the communication between parent and child. In this system we use the text SMS as a mode of communication between parent and child there is minimum chances of failing communication as compared to wi-fi and Bluetooth. It also includes SOS light and BUZZER to provide security to the child in real time situations and it helps to parents to check the condition of child using android application.